Classification of the intensity of interprofessional learning in the context of clinical placements: a proposal based on theoretical foundations in interprofessional education and the results of a narrative review - Richard, Amélie; Perreault, Kadija; Savard, Isabelle; Pinard, Anne-Marie; Careau, Emmanuelle (Canadian Medical Education Journal, 2024)
Context: In terms of interprofessional education (IPE), clinical internships are an interesting opportunity to anchor theoretical knowledge of interprofessionalism in an authentic context. However, even if there is a diversity of experiences described in the scientific literature regarding placement contexts, objectives, and modalities, no taxonomy is adapted to interprofessional internships. Purpose: This article, therefore, proposes an original classification of the intensity of experiences and learning in the context of interprofessional internship experiences based on the modality of learning offered, the degree of experience with patients, the predictability and complexity of tasks required, the focus of learning and the duration of the internship. This classification is grounded in the theoretical foundations of IPE and on data from a narrative review analysis on this subject. Method: A narrative literature review was conducted to target articles on interprofessional internship experiences in health and social services. The analysis process unfolded through iterations between data collection from the articles and analysis based on the theoretical foundations of IPE and expertise of research team members. In accordance with the instructional design research specifications, this process led to the proposal, then to the validation, of a classification of the intensity of interprofessional learning in clinical placements. Results: This classification is composed of four levels suggesting an evolution of the intensity of the educational experience according to the modality and focus of learning, the degree of exposure to patients; the predictability and complexity of the tasks and the duration of the internship. Conclusion: This type of classification will help future instigators of internships to plan, rigorously, and coherently, the progression of learners' knowledge and skills development in IPE based on their program context and goals.